2010
DOI: 10.1007/s10899-009-9169-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Adolescent Problem Gambling, Related Harms and Help-Seeking Behaviours Among an Australian Population

Abstract: Epidemiological studies have consistently reported prevalence rates ranging between 0.9 and 23.5% for problem gambling among young people. With such a large range reported in the literature, it is clear that more research in this area would be of value. The current study investigated the prevalence rate of adolescent gambling and problem gambling and explored types of harm-related and help-seeking behaviours associated with gambling specific to this population in an Australian setting. A self-administered batt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
3
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 32 publications
9
76
3
5
Order By: Relevance
“…La mayoría de los estudios sobre los hábitos de juego de los adolescentes se han realizado en Estados Unidos, Canadá, Reino Unido y Australia (Griffi ths, 2001;Wiebe y Falkowsky-Ham, 2003;Griffi ths et al, 2009;Ipsos MORI, 2009;Splevins et al, 2010;Brunelle et al, 2012;McBride y Derevensky, 2012;Parker et al, 2013), si bien en los últimos años se han llevado a cabo estudios también en diversos países de Europa, como los de Raisamo et al, (2012) en Finlandia; Tsitsika et al, (2011) y Floros et al, (2012 en Grecia, Olason et al, (2011) en Islandia, Erbas y Buchner (2012) en Alemania y Cosenza y Nigro (2015) en Italia. En España, se han realizado algunos estudios sobre la incidencia del juego entre la población en general (Gómez-Yañez, 2015;Jiménez-Murcia et al, 2014) pero pocos sobre el juego entre adolescentes.…”
Section: El Impacto De Los Juegos De Azar En Adolescentesunclassified
See 2 more Smart Citations
“…La mayoría de los estudios sobre los hábitos de juego de los adolescentes se han realizado en Estados Unidos, Canadá, Reino Unido y Australia (Griffi ths, 2001;Wiebe y Falkowsky-Ham, 2003;Griffi ths et al, 2009;Ipsos MORI, 2009;Splevins et al, 2010;Brunelle et al, 2012;McBride y Derevensky, 2012;Parker et al, 2013), si bien en los últimos años se han llevado a cabo estudios también en diversos países de Europa, como los de Raisamo et al, (2012) en Finlandia; Tsitsika et al, (2011) y Floros et al, (2012 en Grecia, Olason et al, (2011) en Islandia, Erbas y Buchner (2012) en Alemania y Cosenza y Nigro (2015) en Italia. En España, se han realizado algunos estudios sobre la incidencia del juego entre la población en general (Gómez-Yañez, 2015;Jiménez-Murcia et al, 2014) pero pocos sobre el juego entre adolescentes.…”
Section: El Impacto De Los Juegos De Azar En Adolescentesunclassified
“…Datos de varios países indican que el juego patológico se inicia a edades tan tempranas como 10 u 11 años (Becoña, 2004;Brunelle et al, 2012;Splevins et al, 2010;Weinberger et al, 2015;Olason et al, 2011). La infl uencia de los padres es muy importante: si los padres juegan con sus amigos o con sus hijos o compran lotería a los hijos o tarjetas de rascar, los hijos desde pequeños ya desarrollan conceptos de juegos de azar observando a sus padres (Lesieur, 2003;Floros et al, 2012).…”
Section: Variables Infl Uyentes Y Factores De Riesgounclassified
See 1 more Smart Citation
“…Research findings suggest that only about 10% of problem gamblers seek help (Ladouceur, et al, 2001) and suggest that shame and humiliation (Pulford et al, 2009) and an inability to recognise when gambling becomes problematic (Splevins, Mireskandari, Claytin, & Blaszczynski, 2010) are contributing factors. All but one participant across the current study indicated that they had been gambling for a number of years and that their gambling habits had gradually, almost insidiously, developed to become problematic.…”
Section: Recognition Of Problem Gambling and Help-seekingmentioning
confidence: 99%
“…Recent data suggests that adolescents are gambling to an increasing extent [1,2], where 36-79% of adolescents report having gambled over the past year [3][4][5]. Although adults tend to gamble more frequently than adolescents, the prevalence of problem gambling (PG) has been estimated to be two to four times higher in youth aged 12 to 17, with rates of Problem Gambling (PG) ranging from 3% to 8% [4,[6][7][8]. Furthermore, an additional 10% to 14% of adolescents who gamble could be considered 'at risk' for PG later in life [9].…”
Section: Introductionmentioning
confidence: 99%